Light rail project in Copenhagen – the Ring 21⁄2 corridor - Andersen, Jonas L. E.; Landex, Alex; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
The need for high class public transport service of the increasing travel across the radial urban structure of the greater Copenhagen region was examined through planning of a light rail. The exact corridor (defined as the Ring 21⁄2 corridor) and alignment of the light rail were documented and the locations of stops were examined through analyses of catchment areas. The timetable of the light rail was determined through travel time and correspondences with other high class public transport lines/corridors. The justification of the light rail was examined through factors like traffic impacts, operation economy, socioeconomics and strategic impacts. The light rail shows a good result on most factors. But it displays socioeconomic non-viability. However, this was expected when using the standard procedures. But the Ring 21⁄2 light rail shows a better socioeconomic result than many other examined light rail projects.